The Subic Bay Sky Park and Ecology Center - Andal, Maria Anginella C.
The Subic Bay Sky Park and Ecology Center is a center for environmental education and stewardship. It was designed to enhance the existing character of the Subic Bay Freeport Zone's central business district (CBD), to further its environmental goals, and to serve as a green infrastructure in the CBD's urban fabric. With the end goal of educating the public about environmental responsibility, the thesis explores different means to engage the public and to protect the SBFZ's natural resources. The project incorporates rood deck gardens, an on-site wastewater treatment, laboratories, and an experiential museum.